Biologia do caranguejo-uçá, Ucides cordatus (Crustacea: Decapoda: Brachyura), na Baía da Babitonga, Santa Catarina, Brasil - Wunderlich, Alison C. [UNESP]; Pinheiro, Marcelo A. A. [UNESP]; Rodrigues, Ana Maria T. (Sociedade Brasileira de Zoologia, 2008)
O objetivo deste estudo é caracterizar pela primeira vez alguns aspectos da reprodução do caranguejo-uçá em manguezais da Baía da Babitonga (Santa Catarina). Além disso, a densidade e o tamanho do estoque deste recurso pesqueiro foram também estimados. Os exemplares foram coletados mensalmente, de maio de 2002 a abril de 2003, em duas áreas distintas: Iperoba e Palmital; um total de 2265 espécimes (1623 machos e 642 fêmeas) foi analisado. Os machos com gônadas maturas foram registrados durante todo o ano, enquanto as fêmeas com gônadas maturas ocorreram em apenas cinco meses. As fêmeas ovígeras foram registradas apenas em dezembro e janeiro. O etograma do fenômeno de migração reprodutiva (andada) esteve em concordância com a maior atividade de caranguejos associada às luas cheias e novas, com maior intensidade em dezembro e janeiro, relacionados ao verão austral. A densidade total no Manguezal de Iperoba foi de 2,05 ± 0,97 ind./m², não diferindo significativamente daquela registrada para o Manguezal do Palmital (2,06 ± 1,08 ind./m²) (p < 0,05). A média global para a estimativa de densidade na Baia da Babitonga foi de 2,05 ± 1,00 ind./m², correspondendo a 1,42 ± 0,89 ind./m² com base nas galerias abertas e 0,64 ± 0,63 ind./m² para as galerias fechadas.

The aim of this work is to characterize, for the first time, aspects of the reproduction of the mandrove-land crab in mangroves of the Babitonga Bay (Santa Catarina). Furthermore, density and stock size of this fishery resource were also estimated. The specimens were sampled from May 2002 to April 2003, from two distinct locations: Iperoba and Palmital; a total of 2265 specimens (1623 males and 642 females) were analyzed. Males with mature gonads were recorded throughout the year, while females with mature gonads were only recorded during a five-month period. Ovigerous females were recorded in December and January. The ethogram of the reproductive migration phenomenon (andada) is in agreement of high crab activity associated to full- and new-moon, with higher intensity during December and January, also related to the austral summer season. The total sampling density on Iperoba Mangrove was 2.05 ± 0.97 individuals.m-2 and did not differ significantly (p < 0.05) from the density recorded on Palmital Mangrove (2.06 ± 1.08 individuals.m-2). The overall average of density estimation at Babitonga Bay was 2.05 ± 1.00 individuals.m-2, which corresponded to the density of open (1.42 ± 0.89 individuals.m-2) and closed burrows (0.64 ± 0.63 individuals.m-2).
Biology of the mangrove uçá crab, Ucides cordatus (Crustacea: Decapoda: Brachyura), in Babitonga Bay, Santa Catarina, Brazil
Keywords: Andada; densidade; pesca; reprodução; Andada; fishery; reproduction; sampling density